x+4=g

Simple and best practice solution for x+4=g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+4=g equation:


Simplifying
x + 4 = g

Reorder the terms:
4 + x = g

Solving
4 + x = g

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + x = -4 + g

Combine like terms: 4 + -4 = 0
0 + x = -4 + g
x = -4 + g

Simplifying
x = -4 + g

See similar equations:

| f(0)=(2x-8) | | -38+9+y=-12+16 | | 5(x-6)-6x(x-5)=x+5-(x-4) | | 1900+5x=2 | | 17x-5=14x-8 | | 7/22x11/35 | | y=2x+5cos^3x | | -3(x+4)=2(x-5) | | 0=x^4-3x^3-8x^2+12x+16 | | 3x-2=-2x-8 | | 30x=6x | | -5(4x+1)-5=-3(x+4)+2x | | 15-6n+2=4n-1 | | y=xsquared+1 | | 11x+13=55 | | -10z=2.7 | | 4-3m=-4m+5 | | 15x=11000 | | 10-6=4 | | 10z=2.7 | | Y=(x-2)squared | | 41790=5+210t | | 8g-4=5(2g+1) | | 4x+7=2x+47 | | 3/2*7/3 | | 65=5+2.5x | | 36+b^2=324 | | (2/9x)-(1/7)=(1/6) | | 6x+4x-4=26 | | 5(4x+5)=-13+18 | | 11x+13=58 | | 3x+25-9=0 |

Equations solver categories